Batch constrained multi-objective Bayesian optimization using the example of ultrasonic wire bonding - Reiling, Fabian; Henke, Christian; Hunstig, Matthias; Gröger, Stefan; Trächtler, Ansgar (2024 IEEE International Conference on Advanced Intelligent Mechatronics (AIM))

Batch Constrained Bayesian Optimization for UltrasonicWire Bonding Feed-forward Control Design - Hesse, Michael; Hunstig, Matthias; Timmermann, Julia; Trächtler, Ansgar (Proceedings of the 11th International Conference on Pattern Recognition Applications and Methods (ICPRAM))
Ultrasonic wire bonding is a solid-state joining process used to form electrical interconnections in micro and power electronics and batteries. A high frequency oscillation causes a metallurgical bond deformation in the contact area. Due to the numerous physical influencing factors, it is very difficult to accurately capture this process in a model. Therefore, our goal is to determine a suitable feed-forward control strategy for the bonding process even without detailed model knowledge. We propose the use of batch constrained Bayesian optimization for the control design. Hence, Bayesian optimization is precisely adapted to the application of bonding: the constraint is used to check one quality feature of the process and the use of batches leads to more efficient experiments. Our approach is suitable to determine a feed-forward control for the bonding process that provides very high quality bonds without using a physical model. We also show that the quality of the Bayesian optimization based control outperforms random search as well as manual search by a user. Using a simple prior knowledge model derived from data further improves the quality of the connection. The Bayesian optimization approach offers the possibility to perform a sensitivity analysis of the control parameters, which allows to evaluate the influence of each control parameter on the bond quality. In summary, Bayesian optimization applied to the bonding process provides an excellent opportunity to develop a feedforward control without full modeling of the underlying physical processes.
Keywords: Bayesian optimization; Wire bonding; Feed-forward control; model-free design

Impact of multi-dimensional vibration trajectories on quality and failure modes in ultrasonic bonding - Schemmel, Reinhard; Eacock, Florian; Dymel, Collin; Hemsel, Tobias; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (International Symposium on Microelectronics)
Ultrasonic joining is a common industrial process. To build electrical connections in the electronics industry, uni-axial and torsional ultrasonic vibration have been used to join different types of workpieces for decades. Many influencing factors like ultrasonic power, bond normal force, bond duration and frequency are known to have a high impact on bond quality and reliability. Multi-dimensional bonding has been investigated in the past to increase ultrasonic power and consequently bond strength. This contribution is focused on the comparison of circular, multi-frequency planar and uniaxial vibration trajectories used for ultrasonic bonding of copper pins on copper substrate. Bond quality was analyzed by shear tests, scanning acoustic microscopy and interface cross-sections.

Using complex multi-dimensional vibration trajectories in ultrasonic bonding and welding - Schemmel, Reinhard; Hemsel, Tobias; Dymel, Collin; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (Sensors and Actuators A: Physical)
Ultrasonic joining is a common industrial process. In the electronics industry it is used to form electrical connections, including those of dissimilar materials. Multiple influencing factors in ultrasonic joining are known and extensively investigated; process parameters like ultrasonic power, bond force, and bonding frequency of the ultrasonic vibration are known to have a high impact on a reliable joining process and need to be adapted for each new application with different geometry or materials. This contribution is focused on increasing ultrasonic power transmitted to the interface and keeping mechanical stresses during ultrasonic bonding low by using a multi-dimensional ultrasonic transducer concept. Bonding results for a new designed connector pin in IGBT-modules achieved by multi- and one-dimensional bonding are discussed.
Keywords: Ultrasonic bonding; Ultrasonic welding; Multi-dimensional bonding; Complex vibration; Multi-frequent; Two-dimensional friction model

Numerical and statistical investigation of weld formation in a novel two-dimensional copper-copper bonding process - Dymel, Collin; Eichwald, Paul; Schemmel, Reinhard; Hemsel, Tobias; Brökelmann, Michael; Hunstig, Matthias; Sextro, Walter ((Proceedings of 7th Electronics System-Integration Technology Conference, Dresden, Germany))
State-of-the-art industrial compact high power electronic packages require copper-copper interconnections with larger cross sections made by ultrasonic bonding. In comparison to aluminium-copper, copper-copper interconnections require increased normal forces and ultrasonic power, which might lead to substrate damage due to increased mechanical stresses. One option to raise friction energy without increasing vibration amplitude between wire and substrate or bonding force is the use of two-dimensional vibration. The first part of this contribution reports on the development of a novel bonding system that executes two-dimensional vibrations of a tool-tip to bond a nail- like pin onto a copper substrate. Since intermetallic bonds only form properly when surfaces are clean, oxide free and activated, the geometries of tool-tip and pin were optimised using finite element analysis. To maximize the area of the bonded annulus the distribution of normal pressure was optimized by varying the convexity of the bottom side of the pin. Second, a statistical model obtained from an experimental parameter study shows the influence of different bonding parameters on the bond result. To find bonding parameters with the minimum number of tests, the experiments have been planned using a D-optimal experimental design approach.
Keywords: ultrasonic wire-bonding; bond-tool design; parameter identification; statistical engineering

Experimental investigations on the impact of bond process parameters in two-dimensional ultrasonic copper bonding - Dymel, Collin; Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias ((Proceedings of 8th Electronics IEEE CPMT Symposium Japan (ICSJ 2018), Kyoto, Japan))
Ultrasonic bonding and welding are common friction based approaches in the assembly of power electronics. Interconnections with cross-sections of 0.3 mm² up to 12 mm² made from copper are well suited in high power applications. For increasing friction energy, which is responsible for bond formation, a two-dimensional vibration approach is applied to newly developed interconnection pins. Using two-dimensional vibration for bonding requires identification of suitable bonding parameters. Even though simulation models of wire bonding processes exist, parameters for the two-dimensional pin-bonding process cannot be derived accurately yet. Within this contribution, a methodology and workflow for experimental studies identifying a suitable bond parameter space are presented. The results of a pre-study are used to set up an extensive statistical parameter study, which gives insights about the bond strength change due to bond process parameter variation. By evaluation of electrical data captured during bonding, errors biasing the resulting shear forces are identified. All data obtained during the experimental study is used to build a statistical regression model suitable for predicting shear forces. The accuracy of the regression model’s predictions is determined and the applicability to predict process parameters or validate simulation models is assessed. Finally, the influence of the tool trajectory on the bond formation is determined, comparing one dimensional, elliptic and circular trajectories.
Keywords: ultrasonic two-dimensional bonding; electrical interconnection; process parameters

Effects of different working frequencies on the joint formation in copper wire bonding - Schemmel, Reinhard; Althoff, Simon; Sextro, Walter; Unger, Andreas; Brökelmann, Michael; Hunstig, Matthias (CIPS 2018 - 10th International Conference on Integrated Power Electronics Systems (CIPS 2018))
Ultrasonic wire bonding is used to connect the electrical terminals of semiconductor modules in power electronics. Mul- tiple inﬂuencing factors in wedge/wedge bonding are known and extensively investigated. A constructively settable but rarely examined parameter is the bonding frequency. In case of bonding on challenging substrates, e.g. supple substruc- tures, a high inﬂuence of the working frequency is observed. The choice of the working frequency is typically based on experimental investigations for a certain component or substrate and needs to be evaluated anew for new applications. A profound understanding of the inﬂuence of the working frequency is required to achieve a reliable bond process and a short process development. Here a generalized model for the numerical simulation of the bond formation with respect to the dynamics of the substructure is presented. The simulation results are compared to experiments using 300 µm copper wire at different working frequencies and geometries of the substructure.

Intelligent Production of Wire Bonds using Multi-Objective Optimization – Insights, Opportunities and Challenges - Unger, Andreas; Hunstig, Matthias; Meyer, Tobias; Brökelmann, Michael; Sextro, Walter (In Proceedings of IMAPS 2018 – 51st Symposium on Microelectronics, Pasadena, CA, 2018)
Ultrasonic wire bonding is an indispensable process in the industrial manufacturing of semiconductor devices. Copper wire is increasingly replacing the well-established aluminium wire because of its superior electrical, thermal and mechanical properties. Copper wire processes differ significantly from aluminium processes and are more sensitive to disturbances, which reduces the range of parameter values suitable for a stable process. Disturbances can be compensated by an adaption of process parameters, but finding suitable parameters manually is difficult and time-consuming. This paper presents a physical model of the ultrasonic wire bonding process including the friction contact between tool and wire. This model yields novel insights into the process. A prototype of a multi-objective optimizing bonding machine (MOBM) is presented. It uses multi-objective optimization, based on the complete process model, to automatically select the best operating point as a compromise of concurrent objectives.
Keywords: wire bonding; multi-objective optimization; process model; copper wire; self-optimization

Multi-dimensional Ultrasonic Copper Bonding – New Challenges for Tool Design - Eichwald, Paul; Althoff, Simon; Schemmel, Reinhard; Sextro, Walter; Unger, Andreas; Brökelmann, Michael; Hunstig, Matthias (IMAPSource)
In power electronics, copper connector pins are e.g. used to connect control boards with power modules. The new chip generation based on SiC and GaN technology increase the power density of semiconductor modules significantly with junction temperatures reaching 200°C. To enable reliable operation at such high temperature, the soldering of these connector pins should be substituted by a multi-dimensional copper-copper bonding technology. A copper pin welded directly on DBC substrate also simplifies the assembly. With this aim, a proper bond tool and a suitable connector pin geometry are designed. This paper presents a two-dimensional trajectory approach for ultrasonic bonding of copper pieces, e.g. connector pins, with the intention to minimize mechanical stresses exposed to the substrate. This is achieved using a multi-dimensional vibration system with multiple transducers known from flip chip bonding. Applying a planar relative motion between the bonding piece and the substrate increases the induced frictional power compared to one-dimensional excitation. The core of this work is the development of a new tool design which enables a reliable and effective transmission of the multidimensional vibration into the contact area between nail-shaped bonding piece and substrate. For this purpose, different bonding tool as well as bonding piece designs are discussed. A proper bonding tool design is selected based on the simulated alternatives. This tool is examined in bonding experiments and the results are presented. In addition, different grades of hardness for bonding piece and substrate are examined as well as different bonding parameters. Optical inspection of the bonded area shows the emergence of initial micro welds in form of a ring which is growing in direction of the interface boundaries with increasing bonding duration.
Keywords: International Symposium on Microelectronics

Piezoelectric Inertia Motors—A Critical Review of History, Concepts, Design, Applications, and Perspectives. - Hunstig, Matthias (Actuators. 2017, 6(1)-7.)
Piezoelectric inertia motors also known as stick-slip motors or (smooth) impact drives use the inertia of a body to drive it in small steps by means of an uninterrupted friction contact. In addition to the typical advantages of piezoelectric motors, they are especially suited for miniaturisation due to their simple structure and inherent fine-positioning capability. Originally developed for positioning in microscopy in the 1980s, they have nowadays also found application in mass-produced consumer goods. Recent research results are likely to enable more applications of piezoelectric inertia motors in the future. This contribution gives a critical overview of their historical development, functional principles, and related terminology. The most relevant aspects regarding their design i.e., friction contact, solid state actuator, and electrical excitation are discussed, including aspects of control and simulation. The article closes with an outlook on possible future developments and research perspectives.

Kupferbondverbindungen intelligent herstellen - Brökelmann, Michael; Unger, Andreas; Meyer, Tobias; Althoff, Simon; Sextro, Walter; Hunstig, Matthias; Biermann, Florian; Guth, Karsten (wt-online)
Leistungshalbleitermodule werden leistungsfähiger, effizienter, kompakter und haltbarer Ziel dieses Innovationsprojekts des Spitzenclusters „it’s OWL – Intelligente Technische Systeme OstWestfalen-Lippe“ ist die Entwicklung von selbstoptimierenden Verfahren, um unter variablen Produktionsbedingungen zuverlässige Kupferbondverbindungen herstellen zu können. Die Ultraschall-Drahtbondmaschine erhält die Fähigkeit, sich automatisch an veränderte Bedingungen anzupassen. Hierzu wird der gesamte Prozess der Ultraschall-Verbindungsbildung modelliert und neueste Verfahren der Selbstoptimierung angewandt. Die Evaluierung erfolgt anhand eines Prototypen in Form einer modifizierten Bondmaschine. Intelligent production of heavy copper wire bonds It is the aim of this innovation-project to develop a self-optimization system for ultrasonic copper wire bonding. It is part of the leading edge cluster “it’s OWL”. The bonding machine will be able to react autonomously to changing boundary conditions to ensure constant and reliable bonding results. For this, the hole bonding process is modeled in great detail and newest self-optimization techniques are utilized. A prototype-system incorporated in a serial machine is used for evaluation.

Reliable Manufacturing of Heavy Copper Wire Bonds Using Online Parameter Adaptation - Meyer , Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Usage of copper wire bonds allows to push power boundaries imposed by aluminum wire bonds. Copper allows higher electrical, thermal and mechanical loads than aluminum, which currently is the most commonly used material in heavy wire bonding. This is the main driving factor for increased usage of copper in high power applications such as wind turbines, locomotives or electric vehicles. At the same time, usage of copper also increases tool wear and reduces the range of parameter values for a stable process, making the process more challenging. To overcome these drawbacks, parameter adaptation at runtime using self-optimization is desired. A self-optimizing system is based on system objectives that evaluate and quantify system performance. System parameters can be changed at runtime such that pre-selected objective values are reached. For adaptation of bond process parameters, model-based self-optimization is employed. Since it is based on a model of the system, the bond process was modeled. In addition to static model parameters such as wire and substrate material properties and vibration characteristics of transducer and tool, variable model inputs are process parameters. Main simulation result is bonded area in the wiresubstrate contact. This model is then used to find valid and optimal working points before operation. The working point is composed of normal force and ultrasonic voltage trajectories, which are usually determined experimentally. Instead, multiobjective optimalization is used to compute trajectories that simultaneously optimize bond quality, process duration, tool wear and probability of tool-substrate contacts. The values of these objectives are computed using the process model. At runtime, selection among pre-determined optimal working points is sufficient to prioritize individual objectives. This way, the computationally expensive process of numerically solving a multiobjective optimal control problem and the demanding high speed bonding process are separated. To evaluate to what extent the pre-defined goals of self-optimization are met, an offthe- shelf heavy wire bonding machine was modified to allow for parameter adaptation and for transmitting of measurement data at runtime. This data is received by an external computer system and evaluated to select a new working point. Then, new process parameters are sent to the modified bonding machine for use for subsequent bonds. With these components, a full self-optimizing system has been implemented.
Keywords: Self-optimization; adaptive system; bond process; copper wire

Validated Simulation of the Ultrasonic Wire Bonding Process - Unger, Andreas; Schemmel, Reinhard; Meyer, Tobias; Eacock, Florian; Eichwald, Paul; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (Wear Modeling in Copper Wire Wedge Bonding. IEEE CPMT Symposium Japan, 2016)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tooltip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard’s wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.
Keywords: the Ultrasonic Wire Bonding Process

Modeling and simulation of the ultrasonic wire bonding process - Meyer, Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (2015 17th Electronics Packaging Technology Conference)
Ultrasonic wire bonding is an indispensable process in the manufacturing of semiconductor components. It is used for interconnecting the silicon die to e.g. connectors in the housing or to other semiconductors in complex components. In high power applications, such as wind turbines, locomotives or electric vehicles, the thermal and mechanical limits of interconnects made from aluminum are nearing. The limits could be overcome using copper wire bonds, but their manufacturing poses challenges due to the harder material, which leads to increased wear of the bond tools and to less reliable production. To overcome these drawbacks, adaptation of process parameters at runtime is employed. However, the range of parameter values for which a stable process can be maintained is very small, making it necessary to compute suitable parameters beforehand. To this end, and to gain insights into the process itself, the ultrasonic bonding process is modeled. The full model is composed of several partial models, some of which were introduced before. This paper focuses on the modularization of the full model and on the interaction of partial models. All partial models are presented, their interaction is shown and the general outline of the simulation process is given.

High-velocity operation of piezoelectric inertia motors: experimental validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Archive of Applied Mechanics)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. It has been shown previously in theoretical investigations that higher velocities and smoother movements can be obtained if these steps do not contain phases of stiction (''stick-slip`` operation), but use sliding friction only (''slip-slip`` operation). One very promising driving option for such motors is the superposition of multiple sinusoidal signals or harmonics. In this contribution, the theoretical results are validated experimentally. In this context, a quick and reliable identification process for parameters describing the friction contact is proposed. Additionally, the force generation potential of inertia motors is investigated theoretically and experimentally. The experimental results confirm the theoretical result that for a given maximum frequency, a signal with a high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion, while the maximum motor force is obtained with signals containing more harmonics. These results are of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Inertia motor; High velocity; Stick-slip motor; Slip-slip operation; Friction parameter identification

Konzeption, Ansteuerung und Eigenschaften schneller piezoelektrischer Trägheitsmotoren - Hunstig, Matthias
Piezoelektrische Trägheitsmotoren nutzen die Trägheit einer bewegten Masse, um diese über einen ununterbrochenen Reibkontakt schrittweise zu bewegen. Wegen ihres einfachen Aufbaus und ihrer guten Miniaturisierbarkeit werden diese Motoren zunehmend in Konsumgütern eingesetzt. Die Geschwindigkeit ist eine wichtige Motorkenngröße, eine allgemeingültige Analyse des Motorprinzips existiert jedoch bisher nicht.Nach einer Definition von Trägheitsmotoren werden anhand eines Modells eines translatorischen piezoelektrischen Trägheitsmotors verschiedene idealisierte Anregungssignale hergeleitet. Eine Analyse des Motorverhaltens zeigt, dass der verbreitete Betrieb von Trägheitsmotoren mit Haft- und Gleitphasen für das Erreichen hoher Geschwindigkeiten ungeeignet ist. Aus den idealisierten Signalen für den schnellen dauergleitenden Betrieb werden frequenzbeschränkte Signale für den Betrieb mit realen Aktoren abgeleitet. Das Verhalten bei Anregung mit diesen Signalen wird bezüglich Geschwindigkeit, Effizienz, Haltbarkeit und Kraft verglichen. Zudem wird ein Verfahren beschrieben, mit dem die Bewegung hochfrequent angeregter Trägheitsmotoren periodenweise berechnet und wichtige Motorkenngrößen direkt berechnet werden können. Zur Validierung der theoretischen Ergebnisse wird ein Versuchsmotor aufgebaut und mit unterschiedlichen Signalen angeregt, es zeigt sich eine gute Übereinstimmung zwischen Messung und Modell. Die Ergebnisse dieser Arbeit geben wertvolle Einblicke in die Funktion schneller Trägheitsmotoren und sind nützlich für ihre weitere Entwicklung und die Erweiterung ihres Einsatzbereichs.
Keywords: Tr{\

Increasing the power of piezoelectric energy harvesters by magnetic stiffening - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
A piezoelectric cantilever beam with a tip mass at its free end is a common energy harvester configuration. This article introduces a new principle of designing such a harvester that increases the generated power without changing the resonance frequency of the harvester: the attraction force between two permanent magnets is used to add stiffness to the system. This magnetic stiffening counters the effect of the tip mass on the efficient operation frequency. Five set-ups incorporating piezoelectric bimorph cantilevers of the same type in different mechanical configurations are compared theoretically and experimentally to investigate the feasibility of this principle: theoretical and experimental results show that magnetically stiffened harvesters have important advantages over conventional set-ups with and without tip mass. They generate more power while only slightly increasing the deflection in the piezoelectric harvester and they can be tuned across a wide range of excitation frequencies.

Enhanced energy harvesting using multiple piezoelectric elements: Theory and experiments - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Power and bandwidth of piezoelectric harvesters can be increased by using multiple piezoelectric elements in one harvester. In this contribution, a novel energy harvesting cantilever array with magnetic tuning including three piezoelectric bimorphs is investigated theoretically and experimentally, with a good agreement between model and experiment. Other than harvester designs proposed before, this array is easy to manufacture and insensitive to manufacturing tolerances because its optimum operation frequency can be re-adjusted after fabrication. Using the superposition principle, the Butterworth-Van Dyke model and a mechanical lumped parameters model, the generated voltage and current are determined analytically. Formulas for calculating the power generated by array harvesters with an arbitrary number of piezoelectric elements connected in series or in parallel are derived. It is shown that optimum harvester design must take both the connected load and the operating frequency into account. Strategies for connecting multiple bimorphs to increase the maximum generated power and/or enhance the bandwidth compared to a single bimorph harvester are investigated. For bandwidth enhancement it is essential that individual rectifiers are used for the bimorphs. An example with three bimorphs shows that, depending on the chosen tuning strategy, the power is increased by about 340% or the bandwidth is increased by about 500%, compared to one single bimorph.
Keywords: Energy harvesting; Cantilever array; Bandwidth; Power increase

Characteristics of Piezoelectric Energy Harvesters in Autonomous Systems - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Proceedings of 10th International Workshop on Piezoelectric Materials and Applications and 8th Energy Harvesting Workshop, Hannover, Germany, 14.-17.7.2013)
A basic autonomous system powered by a piezoelectric harvester contains three components apart from the harvester: a fullwave rectifier, a reservoir capacitor and an electronic device performing the primary task of the system. In this contribution, a model describing the operation of such a system is derived. It is found that in steady-state operation, the piezoelectric harvester experiences two alternating load conditions due to the rectification process. These alternating load conditions can have a significant effect on the operation of the harvester and must be considered in the design of autonomous systems. The results also show that such an autonomous system works efficiently if it is connected to a high impedance load and excited by a frequency matching the anti-resonance frequency of the piezoelectric harvester.
Keywords: Energy harvesting; harvester modeling; load dependence; generated voltage

Leistungs- und Bandbreitensteigerung von Energy-Harvesting-Generatoren für Energieautarke Systeme - Hunstig, Matthias; Al-Ashtari, Waleed; Hemsel, Tobias; Sextro, Walter (9. Paderborner Workshop Entwurf mechatronischer Systeme)